Modern approaches to choosing the method of regional anesthesia during video-assisted thoracoscopic surgery - Yu. A. Ivanishcheva; A. Yu. Zaytsev; A. A. Kavochkin; D. G. Kabakov; M. A. Vyzhigina; K. V. Dubrovin; D. V. Bazarov (Вестник анестезиологии и реаниматологии, 2024)
The objective was to analyze the literature on modern approaches to the choice of regional anesthesia method for thoracoscopic surgical interventions. Materials and methods. A review of the most common approaches to the choice of regional anesthesia method for thoracoscopic surgical interventions was carried out.Results. The analysis of the literature has shown that to date, in the practice of an anesthesiologist and intensivist, there is no single standard for anesthesia of patients during and after thoracoscopic operations, but the use of regional anesthesia methods can increase the positive effects of minimally invasive methods, which include video-assisted thoracoscopic surgeries (VATS). Further studies comparing the efficacy of regional anesthesia methods in thoracic surgery are needed.Conclusion. At the moment, the evidence collected in the world specialized literature confirms that thoracic epidural analgesia (TEA), paravertebral block, erector spinae plane block, and serratus anterior plane block can be considered comparatively effective methods of regional anesthesia in VATS. Meanwhile, high-quality comparative clinical studies that allow us to choose the most effective and safe method of regional anesthesia are limited.